2018
DOI: 10.4184/asj.2018.12.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcomes of Minimally Invasive Stabilization for Spinal Fractures in Patients with Ankylosing Spinal Disorders

Abstract: Study DesignA retrospective study.PurposeTo evaluate the clinical and radiological outcomes of ankylosing spinal disorder (ASD) patients with spinal fractures treated by minimally invasive stabilization (MISt) using percutaneous pedicle screws (PPSs).Overview of LiteratureASDs, such as ankylosing spondylitis (AS) and diffuse idiopathic skeletal hyperostosis (DISH), increase susceptibility to spinal fractures because of extremely decreased spinal flexibility. Such fractures tend to be unstable and, consequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…In these two cases, revision surgery was performed. This was even lower than that described by Lindtner et al [14]. They included nine patients in their study and a CST of 180 min for MIS (range: 92-340 min).…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…In these two cases, revision surgery was performed. This was even lower than that described by Lindtner et al [14]. They included nine patients in their study and a CST of 180 min for MIS (range: 92-340 min).…”
Section: Discussionmentioning
confidence: 63%
“…Kai et al found a blood loss of 104 mL (range: unquantifiable to 480 mL) but did not describe the technique for calculating blood loss in detail [ 14 ]. In our study, we followed the calculation of blood loss by Gombotz et al [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The condition leads to frequent back pain and stiffness of the affected joints. [13] Because there is no cure for the disease itself and because onset typically happens early in young adults who are socially active, AS patients obviously suffer from decreased quality of life (QOL) with long-lasting emotional and functional impairments. [412] These disease characteristics also affect the disease comorbidities: risks of major degenerative diseases—including cardiovascular or cerebrovascular problems—and mental disorders in AS are significantly higher than in the general population, as reported in several published papers.…”
Section: Introductionmentioning
confidence: 99%